Pengaruh Independensi, Etika, Pengalaman, dan Audit Fee terhadap Kualitas Audit : Studi Empiris Pada Auditor Kantor Akuntan Publik Di Pulau Sumatera - Fatimmena, Diva Charisma; Esti Saraswati; Giovanny Bangun Kristianto (Pusat Riset dan Inovasi Nasional, 2026)
Audit quality is an important indicator that reflects the reliability of financial statements and the credibility of information for stakeholders. In the context of the auditing profession within Public Accounting Firms (KAP) in Sumatra, understanding the factors that influence audit quality is highly relevant. This study aims to analyze the effect of independence, ethics, experience, and audit fees on audit quality. The research population includes all auditors working at KAP in Sumatra, with a sample of 111 respondents selected using a purposive sampling technique. The analytical method employed is multiple linear regression with the assistance of SPSS version 25. The results show that independence, ethics, and experience significantly affect audit quality, while audit fees have no significant effect. Simultaneously, all four variables were found to influence audit quality as a whole. These findings contribute to efforts by auditors and KAP to improve the quality of audit services and provide valuable insights for stakeholders in assessing the reliability of financial statements.